Relationship of Speed, Reaction and Concentration to the Achievement of Precision Landing of Gliding Athletes DKI Jakarta - Hidayat Humaid; Tirto Apriyanto; Ghazi Satriando Humaid Junior (Gladi : Jurnal Ilmu Keolahragaan, 2021)
The purpose of this study is to determine the relationship between reaction speed, concentration, and precision landing performance of DKI Jakarta gliding athletes. This study uses the quantitative method by survey technique method. Samples are 13 athletes of DKI Jakarta gliding. In order to get the data, the athlete was tested with reaction speed test, concentration test, and precision landing test. The technique of analyzing the data is correlation technique. The result of this study shown that the correlation between reaction speed, concentration, and precision landing performance is 40.3%, where the reaction speed has 38.3% correlation (strong correlation) to precision landing and concentration has 2.8% correlation to precision landing (weak correlation). So the conclusion is reaction speed has a strong correlation to precision landing while concentration has weak correlation to precision landing.